A Molecular Placeholder Strategy To Access a Family of Transition-Metal-Functionalized Vanadium Oxide Clusters - Kastner, Katharina; Margraf, Johannes; Clark, Timothy; Streb, Carsten (Chemistry - A European Journal, 2014)
Systematic access to metal-functionalized polyoxometalates has thus far been limited to lacunary tungsten oxide and molybdenum oxide clusters. The first controlled, stepwise bottom-up assembly route to metal-functionalized molecular vanadium oxides is now presented. A di-vacant vanadate cluster with two metal binding sites, (DMA)(2)[V12O32Cl](3-) (DMA= dimethylammonium) is formed spontaneously in solution and characterized by single-crystal X-ray diffraction, ESI mass spectrometry, V-51 NMR spectroscopy, and elemental analyses. In the cluster, the metal binding sites are selectively blocked by hydrogen-bonded DMA placeholder cations. Reaction of the cluster with transition metals TM (Fe3+, Co2+, Cu2+, Zn2+) gives access to mono-functionalized vanadate clusters (DMA)[TM(L)V12O32Cl](n-) (L= ligand). Metal binding is accomplished by significant distortions of the vanadium oxide framework reminiscent of a pincer movement. Cluster stability under technologically relevant conditions in the solid-state and solution is demonstrated.
Keywords: functionalization; metal oxide clusters; polyoxometalates; polyoxovanadates; self-assembly